Lagenorhynchus albirostris - James G. Mead; Robert L. Brownell, Jr. (Smithsonian Institution Press, 1993)
Lagenorhynchus albirostris (Gray, 1846). Ann. Mag. Nat. Hist., [ser. 1], 17:84. TYPE LOCALITY: None given in original description, given by Gray (1846:35) as UK, England, "North Sea, coast of Norfolk.", and by Gray (1850) as Great Yarmouth. DISTRIBUTION: North Atlantic: cold-temperate waters; L. albirostris tends to be distributed to the north of L. acutus. STATUS: CITES - Appendix II. SYNONYMS: pseudotursio. Published as part of James G. Mead & Robert L. Brownell, Jr., 1993, Order Cetacea, pp. 349-364 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 353, DOI: 10.5281/zenodo.7352970